PENGGUNAAN METODE JIGSAW DALAM MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XIC DI SMA NEGERI 2 LUMAJANG - Zuhri, Ahmad (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2023)
Based on the results of research observations at SMA Negeri 2 lumajang in class XIC in Islamic religious education subjects do not get serious attention from students, so they often leave class, permission to go to the bathroom, sleep in class as the reason. This research aims to find out about the use of the jigsaw method in increasing the learning activity of grade XIC students in PAI subjects at SMA Negeri 2 Lumajang. By using the Classroom Action Research method. The object of the study was class XIC students of SMA Negeri 2 Lumajang with a total of 36 students. This research was carried out as many as two cycles, each cycle was carried out for 1 meeting. the Classroom Action Research is prepared based on field data using a qualitative approach. The results showed that the learning process using the jigsaw method had a positive impact on increasing learning activity that occurred in students in cycle I and cycle II. The increase in active indicators in cycle I averaged aspects of paying attention / listening to teachers' explanations in cycle I reached 82.8 and in cycle II rose to 84.8, aspects of reading material in cycle I reached 84.7 and in cycle II rose to 86.3 aspects of discussing with groups in cycle I reached 79.9 and in cycle II to 86.5, and aspects of working with groups in cycle I reached 80 and in cycle II to 84.11. The other supporting data is the learning outcomes of students in this case the researcher provides practice questions. And the average of learning outcomes in cycle I was 93.3 and in cycle II increased to 97.7